Infantile onset diabetes mellitus and recurrent hepatic encephalopathy - Muthiah Periyakaruppan; Mahendra Singh Rathore; Gouri Rao Passi (Journal of Pediatric Critical Care, 2019)
We present a case with recurrent hepatic encephalopathy and infantile onset diabetes mellitus where a novel mutation was detected in the EIF2AK3 gene which confirmed the Wolcott Rallison syndrome (WRS) and also briefly review literature related to WRS. Insulin dependent diabetes mellitus (IDDM) diagnosed below the age of 6 months is often due to genetic mutations related to pancreatic development and insulin production. They need to be recognized as some respond to oral drugs like sulphonylureas and need recurrence risk evaluation for the next sibling.